The Effect of the Combination of Endotracheal Tube (ETT) Suction and Semi-Fowler Position on Oxygen Saturation (SPO2) Levels in Patients with Respiratory Failure on Ventilators in the ICU - Diani Yunita Sari; Mohammad Arifin Noor; Dwi Retno Sulistyaningsih (International Journal Of Health Science, 2026)
Patients on mechanical ventilators are at risk of decreased oxygen saturation due to accumulation of secretions in the airway. Endotracheal Tube (ETT) Suction and semi-Fowler positioning are nursing interventions aimed at maintaining and improving patient oxygenation. This study aims to determine the effect of ETT suction and semi-Fowler position on oxygen saturation levels in ventilator-treated patients in the Intensive Care Unit (ICU) . This study used a pre-post design with a sample of 48 ventilator-treated patients in the ICU. Oxygen saturation measurements were performed before and after ETT suction and semi-Fowler positioning. Data were analyzed using the Wilcoxon test . The results showed an increase in oxygen saturation levels after the intervention. The mode value before the intervention was in the mild hypoxemia category, while after the intervention it was in the normal category. The Wilcoxon test results obtained a p value = 0.001 (p < 0.05) which indicated a significant difference between oxygen saturation before and after the intervention . ETT suction and semi-Fowler position have a significant effect on increasing oxygen saturation levels in patients on ventilators in the ICU (p value <0.05).